Unveiling the influence of subjective norms on flood preparedness among household renters: The moderating effect of trust in public protection - Mohd Rozaimy, Ridzuan; Jamal Rizal, Razali; Ju, Soon-Yew; Noor Amira Syazwani, Abd Rahman (Universiti Putra Malaysia Press, 2024)
This research builds on the theory of social norms to investigate the connection between subjective norms, flood preparedness intention, and flood preparedness behavior. Furthermore, this study investigates how trust in public protection moderates the causal link between subjective norms and flood preparedness intention. Purposive sampling was used in this study by administering an online survey to a random sample of 150 tenants in Malaysia's East Coast Region. Structured equation modeling (SEM) utilizing Smart Partial Least Squares (SmartPLS) was then used to analyze the data. The results showed that subjective norms (SN) have a positive relationship with flood preparedness intention (INT) and INT has a positive relationship with flood preparedness behavior (FPB). It is interesting to note that trust in public protection was found to negatively moderate the relationship between SN and INT. The findings will offer valuable insights for policymakers, renters, landlords, and community organizations to develop targeted interventions and bolster flood preparedness among household renters in the East Coast region, ultimately fostering resilience and mitigating the impact of future flood events. This study provides first-hand information on the predictors of flood preparedness behavior among household renters in the East Coast Region, Peninsular Malaysia.